IMF Research Bulletin, July 2009. (IMF Research Bulletin; IMF Research Bulletin ;, 2009)
New Q and A feature in this issue focuses on "Seven Questions about Recessions" (by Marco Terrones); IMF research summaries on financial stress (by Selim Elekdag) and on the real effects of the 2007-08 financial crisis (by Hui Tong); listing of visiting scholars at the IMF during April-June 2009; listing of recent IMF Working Papers; listing of contents of Vol. 56 No. 2 of IMF Staff Papers; listing of recent external publications by IMF staff; and a feature on Staff Position Notes, the IMF's new policy paper series, including a list of recent papers.